MAKNA NORMATIF BESRABES PADA MASYARAKAT MUSLIM MADURA DESA DURIAN KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Yusuf, Selamet Efendi; Marluwi, Marluwi; Ardiansyah, Ardiansyah (Al-Usroh, 2023)
khitbah is the request of a man to a woman with the intention of getting married. The sermon is the first step that must be taken before getting married to open the door to marriage or before entering into a contract. However, the people of Durian Village, Sungai Ambawang Subdistrict, Kubu Raya Regency do not know the term khitbah in the process of getting married, especially the Madurese community, but they are more familiar with a tradition called besrabes, which is the first step taken before taking place wedding. This research will try to further reveal the traditional practices of besrabes carried out by the community, in this context the people in Durian Village, Sungai Ambawang District, Kubu Raya Regency will then be analyzed using al-'urf glasses.